Kingdom of the Netherlands-Netherlands : Publication of Financial Sector Assessment Program Documentation: Technical Note on Financial Sector Supervision: The Twin Peaks Model. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The global financial crisis has tested the effectiveness of supervision under the 'Twin Peaks' model. The crisis revealed the strengths of the 'Twin International Peaks' model, as decisions were able to be made in a timely manner to contain the crisis, and clear divisions of powers and responsibilities were instrumental in ensuring effective coordination between key agencies. However, the crisis also exposed certain areas where improvements could strengthen the 'Twin Peaks' framework. Intensive and well-focused efforts are being made to strengthen the supervisory framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet